Non-Pharmacological Treatments of Psoriasis in Persian Medicine a Narrative Review - Farshad Mohammadian Rasanan; Hoorieh Mohammadi Kenari; Mohammadreza Ghassemi; Ali Jabbari Sabbagh; Jale Aliasl; Ali Ghobadi (Korean Pharmacopuncture Institute, 2022)
Psoriasis is a chronic disease that has no definitive cure. In this review study, the main sources of Persian Medicine (PM) such as the Canon of Medicine (by Avicenna) and Al-Havi (by Rhazes) were assessed to identify non-pharmacological treatments for psoriasis. Several treatments that are recommended for this disease include nutritional advice, lifestyle modifications, and manipulation therapy such as wet cupping (Hijamah), leech therapy, and phlebotomy (Fasd). These recommendations may help to prevent recurrence and be useful in improving psoriasis. The efficacy of PM recommendations to improve psoriasis should be evaluated in future studies.